A Critical Review of Wansbrough’s Qur’anic Theory through Quraish Shihab’s Epistemology - Muchammad Agiel Kholid Putra; Sandi Ferdy Yulianto (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT The authenticity and codification of the Qur’an remain central debates in contemporary Qur’anic studies. John Wansbrough’s historical theory posits the Qur’an as a product of prolonged communal redaction, completed long after the Prophet Muhammad. In contrast, M. Quraish Shihab argues for a systematic transmission grounded in revelation, collective memorization, and historical verification. This study critically examines the methodological assumptions of Wansbrough’s theory and reconstructs Shihab’s epistemological framework on Qur’anic authenticity and codification. Using qualitative hermeneutic library research with a comparative approach, this study analyzes primary and secondary sources through textual analysis, codicology, and qirāʾāt studies. Findings show that Wansbrough’s theory suffers from three main weaknesses: uncritical application of biblical criticism to Islamic tradition, neglect of oral transmission, and excessive historical inference with limited manuscript engagement. Conversely, Shihab develops an integrative epistemology combining revelation, rational inquiry, and linguistic analysis. The critical dialogue between both perspectives leads to a Synthetic Qur’anic Epistemology comprising transcendental, historical-transmissional, and textual-linguistic dimensions. This study contributes an interdisciplinary model integrating philology, codicology, radiocarbon analysis, and sanad-qirāʾāt studies to balance academic rigor with the epistemological foundations of Islamic revelatory tradition. Keywords : John Wansbrough; M. Quraish Shihab; Qur’anic authenticity; Qur’anic codification; Synthetic Qur’anic Epistemology